Strength and Explosive Power Training Supports Volleyball Smash Jumps: Latihan Kekuatan Dan Daya Ledak Menunjang Lompatan Smash Bola Voli - Raga Kurniawan; Jhony Hendra; Khairul Saleh; Ikhsan Maulana Putra; Raja Bani Pilitan (Academia Open, 2025)
General Background: Volleyball requires strong physical conditioning, particularly explosive jumping ability, to execute effective smashes. Specific Background: Many female players at Club Bungo Indah struggle with insufficient leg strength and jump height, limiting their smash performance. Knowledge Gap: Previous studies have shown the benefits of strength and plyometric training, but limited evidence exists on its application in female club-level athletes with short training durations. Aims: This study aimed to examine whether structured strength and explosive power training improves jumping ability during smashes in volleyball. Results: Using an experimental pretest-posttest design with 15 female players, vertical jump measurements analyzed with a paired sample t-test showed a significant improvement (t = 6.883, p < 0.05). The average jump height increased by 5.53 cm after 14 training sessions. Novelty: This study highlights the effectiveness of a relatively short-duration program specifically applied to female volleyball players in a local club context. Implications: Findings provide practical guidance for coaches to incorporate strength and explosive power training into regular programs, demonstrating that even with simple facilities and short periods, meaningful performance gains can be achieved. Highlight: Training improved players’ jump height by 5.53 cm. Strength and explosive power training benefits female volleyball athletes. Practical program can be applied with simple facilities. Keywords: Strength Training, Explosive Power, Volleyball, Smash, Jump